Stakeholder Perspectives on Opportunities and Challenges in Achieving Sustainable Growth of the Blue Economy in a Changing Climate - Hoerterer, Christina; Schupp, Maximilian F.; Benkens, Andreas; Nickiewicz, Dustin; Krause, Gesche; Buck, Bela H. (Frontiers in Marine Science, 2020)
Abstract Coastal marine environments provide livelihoods as billions of people around the world depend greatly on sustainability efforts in the Blue Economy. In this study, we investigated how stakeholders from important Blue Economy sectors along the German North Sea coast perceive the impacts of climate change on their daily work life and the growth of the Blue Economy. In a two-stage approach we first conducted two stakeholder workshops with representatives from the regional sea food sector, science, NGOs and local authorities, in order to identify important issues linked to climate change affecting environment, society, economy and policy. In the second stage, we conducted semi-structured interviews with key knowledge holders from the Blue Economy, to evaluate and validate the most important issues identified during the first stage, and the impacts on the respective sectors. The workshop participants identified perceptible effects of climate change on their marine environment. Early career scientists showed that they possess a clear focus on measures for climate change adaptation, transdisciplinary approaches and knowledge transfer. The interviews revealed that the climate change effects could be perceived as both negative and positive, depending on the sector. Other issues, especially political decisions and developments are perceived to have a greater immediate impact on the Blue Economy than the slow progress of climate change effects. Additionally, increased human activities, in the form of new or intensified uses like marine renewable energy generation, have a greater influence and lead to conflicts between the Blue Economy sectors. Our study showed that economic and societal stakeholders in Germanys North Sea region are aware of climate change and already perceive its effects on their businesses. Synergies and conflicts between the sectors and political decisions might influence sustainable growth of the Blue Economy in highly contested regions, suh as the North Sea basin, much stronger than the effects of climate change. This calls for a more flexible and adaptive approach to policymaking, taking into account the changing environmental, social and economic realities.